Farmers Group Development Potential Through the Make Straw Compost in Nagari Lima Kaum Tanah Datar Regency West Sumatra - Ratna Wilis; Widya Prarikesslan; Erna Juita; Irda Suryani; Pudia M Indika (Science and Environmental Journal for Postgraduate, 2020)
TanahDatarRegencyistheonehaspopulation withprofessionasthefarmer,andwhichonetheproduct ispaddy.Thefarmerhasproblemstobuyfertilizer,theeconomicbackgroundandthemfinancial,andthencauses the price of fertilizer so high, the product is limited, it was not support to increasing paddy product from farming area. For full fill the hulled rice necessary more rise day after day so really important to make new innovation to cultivation paddy plant. One of that it must give more value and rise of efficiency in agricultural, one of the solution is using the straw waste as theingredient.Some method has offered to realization the empowerment program is, training, lecture and practice, such: (1) case study, (2) practice and explanation how to make compost (organic fertilizer) use the straw waste, (3) brainsstorming/collectionallofidea,opinion, fromthefarmer,(4)doingdiscussion betweenfarmerandspeaker or the government, (5) lecture all of topic the program about the work flow, plan, to be solution by the farmer, farmer team of theproblems.